Climate change 1995 : impacts, adaptations, and mitigation : summary of policymakers (WMO GenevaCH)
Represents the formally-agreed statements of the IPCC concerning current understanding of the impacts of climate change, adaptative responses, and measures that could mitigate future greenhouse gas emissions.
Contribution of Working Group II to the second assessment report of the Intergovernmental Panel on Climate Change